The impact of Schistosoma japonicum infection and treatment on ultrasound-detectable morbidity: a five-year cohort study in Southwest China. - Elizabeth J Carlton; Michelle Hsiang; Yi Zhang; Sarah Johnson; Alan Hubbard; Robert C Spear (Public Library of Science (PLoS), 2010)
Ultrasonography allows for non-invasive examination of the liver and spleen and can further our understanding of schistosomiasis morbidity.We followed 578 people in Southwest China for up to five years. Participants were tested for Schistosoma japonicum infection in stool and seven standard measures of the liver and spleen were obtained using ultrasound to evaluate the relationship between schistosomiasis infection and ultrasound-detectable pathology, and the impact of targeted treatment on morbidity. Parenchymal fibrosis, a network pattern of the liver unique to S. japonicum, was associated with infection at the time of ultrasound (OR 1.40, 95% CI: 1.03-1.90) and infection intensity (test for trend, p = 0.002), adjusting for age, sex and year, and more strongly associated with prior infection status and intensity (adjusted OR 1.84, 95% CI: 1.30-2.60; test for trend: p<0.001 respectively), despite prompt treatment of infections. While declines in parenchymal fibrosis over time were statistically significant, only 28% of individuals with severe parenchymal fibrosis (grades 2 or 3) at enrollment reversed to normal or grade 1 within five years. Other liver abnormalities were less consistently associated with S. japonicum infection.Parenchymal fibrosis is an appropriate measure of S. japonicum morbidity and can document reductions in disease following control efforts. Other ultrasound measures may have limited epidemiological value in regions with similar infection levels. Because severe fibrosis may not reverse quickly following treatment, efforts to reduce exposure to S. japonicum should be considered in combination with treatment to prevent schistosomiasis morbidity.